High quality acquisition of surface electromyography – conditioning circuit design - Shobaki, Mohammed M.; Abdul Malik, Noreha; Khan, Sheroz; Nordin, Anis Nurashikin; Haider, Samnan; Larbani, Sofiane; Arshad, Atika; Tasnim, Rumana (IOP Publishing, 2013)
The acquisition of Surface Electromyography (SEMG) signals is used for many applications including the diagnosis of neuromuscular diseases, and prosthesis control. The diagnostic quality of the SEMG signal is highly dependent on the conditioning circuit of the SEMG acquisition system. This paper presents the design of an SEMG conditioning circuit that can guarantee to collect high quality signal with high SNR such that it is immune to environmental noise. The conditioning circuit consists of four stages; consisting of an instrumentation amplifier that is used with a gain of around 250; 4th order band pass filter in the 20-500Hz frequency range as the two initial stages. The third stage is an amplifier with adjustable gain using a variable resistance; the gain could be changed from 1000 to 50000. In the final stage the signal is translated to meet the input requirements of data acquisition device or the ADC. Acquisition of accurate signals allows it to be analyzed for extracting the required characteristic features for medical and clinical applications. According to the experimental results, the value of SNR for collected signal is 52.4 dB which is higher than the commercial system, the power spectrum density (PSD) graph is also presented and it shows that the filter has eliminated the noise below 20 Hz.